Containment control of multi-agent systems via a disturbance observer-based approach. Issue 5 (March 2019) - Han, Tao; Li, Juan; Guan, Zhi-Hong; Cai, Chang-Xin; Zhang, Ding-Xue; He, Ding-Xin
Abstract: This paper deals with the containment control problem for multi-agent systems with exogenous disturbances. A disturbance observer-based control approach is employed to estimate the disturbances generated by an exogenous system. Consequently, distributed disturbance observer-based containment control protocols are proposed by using the state feedback control and the output feedback control, respectively. Furthermore, with the help of algebraic graph theory and Lyapunov stability theory, sufficient conditions are established to ensure that multi-agent systems with exogenous disturbances can achieve containment control via the disturbance observer-based approach. Finally, the effectiveness of our theoretical results is verified by providing numerical simulation examples.